Walking for transport and all-cause mortality: a prospective cohort study of Australian community-dwelling older adults - Rory Wolfe; Neville Owen; Ben Beck; Yang Chen; David W Dunstan; Alice Owen; Robyn L Woods; Danijela Gasevic; Joanne Ryan; Shivangi Shah; Carlene Britt (BMJ Public Health)
Background Walking for transport may prolong survival in younger and middle-aged adults; however, evidence for older adults is scarce. We examined a prospective relationship between transport-related walking and all-cause mortality among adults aged 70 years and over.Methods Community-dwelling, apparently healthy older adults (n=11 539; mean age 75.1 years, 53.1% females), participants of the ASPirin in Reducing Events in the Elderly Longitudinal Study of Older Persons, reported their frequency of transport-related walking (never, rarely/once a week, more than once a week or every day). All-cause mortality was verified by two independent sources. Cox proportional-hazards models (HR and 95% CI) assessed the association between transport-related walking and all-cause mortality.Results Of participants, 44.1% reported walking every day, 31.5% more than once a week, 21.7% rarely or once a week and 2.7% never engaged in transport-related walking. During the median follow-up of 8.6 years (IQR: 7.4–10.1), 1599 participants (13.9%) died. Compared with those who reported never walking for transport, the risk of all-cause mortality was lower for those walking rarely or once a week (HR 0.73, 95% CI 0.56 to 0.96); more than once a week (HR 0.76, 95% CI 0.59 to 0.99) and every day (HR 0.74, 95% CI 0.57 to 0.96). Analyses were adjusted for age, sex, education, smoking, alcohol consumption, living status, rurality, household income, socioeconomic status, chronic conditions, body mass index and overall physical activity levels.Conclusions Engaging in any weekly transport-related walking helps older adults prolong survival. Public health campaigns and urban planning should promote and support transport-related walking to boost physical activity levels of older adults and support healthier ageing.